Creating a Global Learning Ecosystem on Campus (Comparative & International Education Series, 2021)
Bridging the knowledge gap between students who study abroad and student who do not is something with which institutional leaders struggle, even though many colleges and universities tout graduates who are prepared for personal and professional lives in a global context. Internationalization at Home (IaH) focuses on those aspects of international education that can be infused into the campus environment – both in and out of the classroom – to provide a global learning ecosystem for all students.  Beelan and Jones (2015) offered an updated definition of Internationalization at Home that provided clarity and stressed intentionality:  “Internationalization at Home is the purposeful integration of international and intercultural dimensions into the formal and informal curriculum for all students within domestic learning environments” (p. 69). This proposed chapter will highlight the literature (literature review) around the complex topic of IaH and consider the many components that work together within this global learning ecosystem, including:  • university leadership drivers including mission, vision, and strategic planning,• curriculum infusion of global contexts including international virtual exchange, faculty training, and learning outcomes• international scholars and foreign-born faculty, • faculty policies and practices, • co-curricular programs, • international students studying on campus, and• diversity and inclusion efforts to name a few  The chapter will conclude with discussion and steps institutions can take in developing a global learning ecosystem.  Melissa K. Mace is a scholar-practitioner with research interests in comprehensive internationalization, internationalization at home, and curriculum integration of global contexts. She developed the Institutional Assessment Rubric on Comprehensive Internationalization in Higher Education (IARCIHE), a tool to assist institutions in conducting a baseline analysis of comprehensive internationalization, set strategic goals, and track progress over time. She holds a doctorate of education in higher education leadership, a master of science in student affairs in higher education, and a bachelor’s degree in communication.